On the Intraindividual and Gender Variability of Haemostatic Components - Blombäck, M; Eneroth, P; Landgren, B-M; Lagerström, M; Anderson, O (Thrombosis and Haemostasis, 1992)
The intraindividual variability in terms of coagulation analyses was explored in 10-16 samples collected from each of 15 women during one menstrual cycle. For comparison, six men were sampled six times during a period of 30 days. The following variables were analysed: FVII, FVIII, FX, vWF:Ag, vWF: ristocetin cofactor, fibrinogen, antithrombin, plasminogen and antiplasmin.The results demonstrated mean coefficients of variation ranging between 4.5 (plasminogen) and 20.7 (vWF:Ag). In certain individuals, the intraindividual variability amounted to nearly 40%, in particular in the assays of FVIII and vWF: Ag. No direct relation between these two factors and oestradiol, progesterone or testosterone levels could be observed in our individuals.The implications of these variations are discussed in terms of disease prediction and diagnosis of coagulation disorders.